The Use of Deceased Donor Organs in Kidney Transplantation - Chakravorty, Triya; Dengu, Fungai (Journal of the Nuffield Department of Surgical Sciences, 2022)
Kidney transplantation is considered the optimal therapy for end-stage renal disease (ESRD). It improves quality of life and survival and is less of a financial burden in comparison to dialysis. However, there is a national shortage of organ donors, which hinders the success of kidney transplantation and can result in long waiting times. The continued mismatch between donor supply and demand has led to the exploration of new avenues of organ acquisition. This report will describe the case of Mr A, who had a kidney transplant in 2020. This report will review the recent literature comparing the different types of deceased donor organs available for transplant, and discuss the strategies used to increase donor organ supply.